2020
DOI: 10.1080/17538068.2020.1842843
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes, and practices towards COVID-19 among Colombians during the outbreak: an online cross-sectional survey

Abstract: Background: Preventing the spread of COVID-19 requires the modification of behavior, including social distancing, mask-wearing, and regular handwashing. Modifying behavior requires understanding people's knowledge, attitudes, and practices (KAPs) regarding health threats. We explored KAPs among Colombians to examine whether KAPs affect adherence to recommended practices during the initial outbreak. Methods: We distributed a cross-sectional, internet-based questionnaire using referral network techniques. The qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 40 publications
(39 reference statements)
1
13
0
Order By: Relevance
“…Specific areas where knowledge could be improved in Venezuela are the differences in symptoms between the common cold and COVID-19, as well as the inutility of antibiotics in preventing COVID-19 and the utility of wearing a mask. Significantly, where Bates et al’s [ 47 , 52 ] previous studies found few associations between knowledge and preventive practices, our data reveals that Venezuelans who are more knowledgeable of COVID-19 are more likely to wash their hands correctly, more likely to wear masks when in public, and less likely to improperly take antibiotics. Because these practices correspond fairly well to knowledge gaps among Venezuelans, they present clear and direct targets for educational messaging, and this kind of scientifically accurate messaging, if properly disseminated, could have a substantial impact on improving healthy practices [ 53 55 ].…”
Section: Discussionmentioning
confidence: 38%
See 2 more Smart Citations
“…Specific areas where knowledge could be improved in Venezuela are the differences in symptoms between the common cold and COVID-19, as well as the inutility of antibiotics in preventing COVID-19 and the utility of wearing a mask. Significantly, where Bates et al’s [ 47 , 52 ] previous studies found few associations between knowledge and preventive practices, our data reveals that Venezuelans who are more knowledgeable of COVID-19 are more likely to wash their hands correctly, more likely to wear masks when in public, and less likely to improperly take antibiotics. Because these practices correspond fairly well to knowledge gaps among Venezuelans, they present clear and direct targets for educational messaging, and this kind of scientifically accurate messaging, if properly disseminated, could have a substantial impact on improving healthy practices [ 53 55 ].…”
Section: Discussionmentioning
confidence: 38%
“…Because COVID-19 is a regional threat in Latin America, identifying similarities and differences between KAPs among different national populations may allow Ministries of Health to learn best practices from other nations or identify unique intervention points for their people. In this instance, similarities and differences in KAPs in Venezuela and in two other Latin American states–Colombia and Ecuador–can be identified because our methodology and sample are similar to KAP investigations previously conducted in Colombia and in Ecuador [ 47 , 52 ]. Not only are the current study’s demographic characteristics similarly distributed in terms of age, gender, socioeconomic status, and urban/rural residency, but eleven of twelve knowledge items, both attitudinal items, and three of the four practice items are identical to Bates et al’s studies.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Since the beginning of the pandemic, several empirical treatments and homemade remedies have been deemed effective to battle infection, notwithstanding the lack of supporting information and the disregarding of potential side effects [ 34 , 35 ]. In addition, the severe consequences left by the first COVID-19 outbreak have deteriorated optimistic attitudes among the public, which has prompted a rise in the popularity of holistic medicine (pseudo medicine) and pseudoscience [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…With respect to patient attitudes, confidence that the Venezuelan government can effectively control the virus (42.8%) was greater than in Peru (23.1%) (11); however, it was much less than in China (97.1%) and Tanzania (96%) (14,19), significantly inferior to other countries of the area, such as Colombia (51,3%), Paraguay (66%), and Ecuador (63%) (26)(27)(28), and had similar results to those found in Brazil (41%) (29). This could suggest discontent and a high sense of risk by the surveyed population.…”
Section: Discussionmentioning
confidence: 99%